MAKNA DAN NILAI SIMBOLIS UPACARA KEMATIAN YANG DILAKSANAKAN OLEH MASYARAKAT DESA SELEMAN KABUPATEN KERINCI-JAMBI - Mukhsin Patriansyah (UNIVERSITAS INDO GLOBAL MANDIRI, 2017)
Human beings are cultured, this is manifested because of an interaction between humans and the universe in which it is located On that basis then the diversity of cultures of ethnic groups around the world according to their mindset by learning from the environment in which they live. Culture is created by human activity. This human activity can be seen from various aspects such as marriage, ceremonies of death, art, customs and so forth. Man as a creature that creates culture is an inseparable unity, although man will die later, but what he has obtained will be passed on to his future generations. For the villagers of Seleman, death is not just a matter of the exodus of the spirit, but it is also a sacred event that becomes the entrance of man to the next. Death is not the end of the journey of human life, but it is the beginning of another life. As the beginning of a new life, it is natural to prepare all the necessities needed in a new life. The ceremony of death conducted by the community of Seleman Village Kerinci-Jambi Regency, if examined deeply, then it contains values and concepts in social science that can be used as a reference in life together and the provision of life in the future. These values include mutual cooperation, humanity, andreligion. The value of mutual cooperation and humanity is reflected in the behavior of the people around the family who are experiencing the disaster. In this case, without being asked, every family came to express their condolences and help by sending one of their members (women) to the house of a mourning family carrying some rice. Meanwhile, the men, in addition to assisting in the preparation of burials, also prepared the woodsneededforcookinginordertosave (Festivity). Keywords : Culture, Death Ceremony, Seleman, Value, Mutual Cooperation.